2021
DOI: 10.3390/jcm10184228
|View full text |Cite
|
Sign up to set email alerts
|

The Disproportionate Increase of the Intraoperative Flexion and Extension Gap Space after Posterior Cruciate Ligament Resection in Total Knee Arthroplasty

Abstract: Purpose: Maintaining gap balance is critical for total knee arthroplasty (TKA). This study aimed to elucidate if the extension–flexion gaps would be changed with posterior cruciate ligament (PCL) intact (PI) and PCL resection (PR) during TKA. The flexion gaps were measured using two methods, open-(Fo) and closed-chain position (Fc), based on the definition of kinetic chain position, respectively. Methods: This retrospective study enrolled a total of 33 patients who underwent posterior-stabilized (PS) TKA for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Then whether through trauma or attrition, the PCL failed leading to an unbalanced flexion gap leading to the observed sagittal plane instability. 9,10 This study has several limitations. First, it was singlecenter study, and the number of participants was small with only 26 participants in total.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Then whether through trauma or attrition, the PCL failed leading to an unbalanced flexion gap leading to the observed sagittal plane instability. 9,10 This study has several limitations. First, it was singlecenter study, and the number of participants was small with only 26 participants in total.…”
Section: Discussionmentioning
confidence: 95%
“…Then whether through trauma or attrition, the PCL failed leading to an unbalanced flexion gap leading to the observed sagittal plane instability. 9 , 10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, PCL resection has a greater effect on the opening of the flexion gap, potentially causing a flexion-extension mismatch. [13][14][15]17,19,20 Kadoya et al 14 analyzed 30 patients with PCL resection in TKA and found that the flexion gap significantly increased on the medial and the lateral sides (4.8 and 4.5 mm, respectively), but that there was no effect on the extension gap. Warth et al 17 reviewed the outcomes of 129 standardized TKAs and reported that the tibiofemoral gap increased progressively from extension to flexion after PCL resection.…”
Section: Flexion and Extension Gapsmentioning
confidence: 99%
“…Warth et al 17 reviewed the outcomes of 129 standardized TKAs and reported that the tibiofemoral gap increased progressively from extension to flexion after PCL resection. Tu et al 19 reported that in 33 patients with knee osteoarthritis, the major result of PCL release was the creation of a larger flexion gap. As demonstrated in our study, ACL resection did not affect both the extension and flexion gaps, while the release of the PCL significantly increased the flexion gap, but did not have any measurable effect on the extension gap.…”
Section: Flexion and Extension Gapsmentioning
confidence: 99%